Diboryldiborenes: π‐Conjugated B4 Chains Isoelectronic to the Butadiene Dication. Issue 32 (15th July 2018) - Hermann, Alexander; Cid, Jessica; Mattock, James D.; Dewhurst, Rian D.; Krummenacher, Ivo; Vargas, Alfredo; Ingleson, Michael J.; Braunschweig, Holger
Abstract: B(sp 2 )–B(sp 3 ) diborane species based on bis(catecholato)diboron and N‐heterocyclic carbenes (NHCs) underwent catechol/bromide exchange selectively at the sp 3 ‐hybridized boron atom. The reduction of the resulting 1, 1‐dibromodiborane adducts led to reductive coupling and isolation of doubly NHC‐stabilized 1, 2‐diboryldiborenes. These compounds are the first examples of molecules exhibiting π‐electron delocalization over an all‐boron chain. Abstract : Occupy pi street : The reduction of NHC‐stabilized 1, 1‐dibromodiborane adducts leads to reductive coupling and isolation of doubly NHC‐stabilized 1, 2‐diboryldiborenes. These compounds are the first examples of molecules exhibiting π‐electron delocalization over an all‐boron chain. NHC=N‐heterocyclic carbene.